What does “Middle East Studies” mean in Latin America? A Special Issue - Ferabolli, Silvia; Amaral, Rodrigo (Conjuntura internacional, 2025)
Building on the extensive social, political, and economic relationships between Latin America and the Middle East, a fundamental question arises: “What does ‘Middle East Studies’ mean in Latin America?” While this may initially appear to be a bold inquiry, it should be understood metaphorically—as an invitation to explore how Latin American scholars conceptualize, interpret, and engage with the Middle East through distinct regional lenses. This question serves as the intellectual foundation of this Special Issue, which seeks to offer insight into the diverse methodological, theoretical, and empirical approaches that define Latin American research on the Middle East.